Non-stationary Natural Mortality Influencing the Stock Assessment of Atlantic Cod (Gadus morhua) in a Changing Gulf of Maine - Chen, Ning; Sun, Ming; Zhang, Chongliang; Ren, Yiping; Chen, Yong (Frontiers in Marine Science, 2022)
Climate changes have increasingly driven diverse biological processes of fish and lead to non-stationary dynamics of populations. The Gulf of Maine (GOM) is vulnerable to climate change, which should be considered in fisheries stock assessment and management. This study focuses on the effects of possible non-stationary natural mortality (M) on the stock assessment of Atlantic cod (Gadus morhua) in GOM. We evaluated different assumptions about stationary and non-stationary M driven by sea surface temperature (SST) using a simulation approach. We found that adopting non-stationary M could effectively improve the quality of stock assessment compared to the commonly used stationary assumption for the GOM cod. Non-stationary scenario assuming a nonlinear relationship between SST and M had the lowest estimation errors of spawning stock biomass and fishing mortality, and the younger and the older age-groups tended to be less accurately estimated. Different assumptions in M led to diverged estimates of biological reference points and yielded large differences in determination of stock status and development of management advices. This study highlights the importance of including non-stationary vital rates in fisheries assessment and management in response to changing ecosystems.